Valor nutritivo da silagem de maniçoba (Manihot pseudoglaziovii) com e sem fubá de milho como aditivo - Backes, Alfredo Acosta (2014)
With the objective to study the nutritional value of maniçoba in silage form, with or without corn meal, this study was undertaken. The used treatments were: maniçoba silage with four levels (0; 10; 20 and 30) of addition of corn meal, with five repetitions for treatment. The pH of the silage remained between 4.1 to 4.3 which would be satisfactory indicating that there was a good lactic fermentation, independent in the addition of corn meal. For DIVMS occurred significant increase values (P < 0.05) due to the increment in the addition of corn meal, and the inclusion of 20% corn proved to be capable of providing highest value of this parameter (65.1%). The acetic and butyric acids concentrations were reduced in the measure in that growing levels were added of additives. The lactic acid concentrations were considered satisfactory in all of the treatments. There was a significant decrease (p<0.05) in NDF and ADF with the inclusion of corn meal. However the lowest value for traits was observed in treatment with 20% addictive. It is concluded that maniçoba silage is an alternative source of good nutritional value, especially when added to corn meal as additive. The better level of inclusion of corn meal in maniçoba silage is 20%.